Methane and nitrous oxide dissolved gas concentrations in seawater from the North American Arctic Ocean (2015–2018) - Cara C M Manning; Zhiyin Zheng; Lindsay Fenwick; Ross D McCulloch; Ellen Damm; Robert W Izett; William J Williams; Sarah Zimmermann; Svein Vagle; Philippe Daniel Tortell (PANGAEA, 2022)
This dataset contains methane and nitrous oxide dissolved gas concentration, dissolved methane carbon isotope, and ancillary hydrographic data from research cruises in the North American Arctic Ocean between 2015-2018. Ocean samples for methane and nitrous oxide analysis were collected from Niskin bottles mounted on a CTD rosette. Water was collected into glass serum bottles and allowed to overflow three times before preserving with mercuric chloride and sealing with with butyl rubber stoppers and aluminum crimp seals. Gas concentrations were determined using a purge and trap system coupled to a gas chromatograph/mass spectrometer, following the method of Capelle et al. (2015). Equilibrium dry atmospheric concentrations were 328.25, 329.14, 330.11, and 330.96 ppb for N2O and 1919.64, 1933.67, 1934.92, and 1933.50 ppb for CH4 in 2015, 2016, 2017, and 2018, respectively. Equilibrium dissolved concentrations were calculated from the measured temperature and salinity following Wiesenburg and Guinasso (1979) for CH4 and Weiss and Price (1980) for N2O. Equilibrium concentrations were calculated based on sample temperature and salinity and the atmospheric N2O or CH4 concentrations measured at Barrow, Alaska by the NOAA Earth System Research Laboratory Global Monitoring Division (Dlugokencky et al., 2020a,b), with corrections to local sea level pressure and 100% humidity. Oxygen concentration was determined using an oxygen sensor mounted on the Niskin rosette, calibrated with discrete samples analyzed by Winkler titration. The mixed layer depth was defined based on a potential density difference criterion of 0.125 kg/m^3 relative to the density at 5 m depth, using CTD profiles binned to 1 m. The mixed layer depth was set to 5 m as a minimum. For methane δ13C, samples were pre-concentrated through a purge and trap system (Finnigan PreCon Trace Gas Pre-Concentrator) and measured with a Finnigan Delta XP Plus mass spectrometer following the method of Damm et al. (2015).
In: Manning, CCM et al. (2022): Methane and nitrous oxide dissolved gas concentrations and sea-air fluxes from rivers and seawater in the North American Arctic (2015–2019) [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.941201